Health-Related Challenges and Coping Strategies Among Women During Pandemics: A Systematic Review of Qualitative Studies - Sahay, Mili Roopchand; Dubey, Shubhankar; Sahoo, Rakesh Kumar; Kanungo, Srikanta; Sahoo, Krushna Chandra; Pati, Sanghamitra (Frontiers in Health Services, 2022)
Equality and empowerment for women are among the 17 Sustainable Development Goals (SDGs 5). Although women were confronted with more challenges in various ways during pandemics; however, there is hardly any systematic synthesis of evidence on women's health-related challenges during pandemics. We reviewed the health challenges faced by women during the pandemic. We searched MEDLINE, PsycINFO, and CINAHL following PRISMA guidelines. We identified 2,831 studies, of which we included 17. Reproductive health, psychosocial health, and gender-based violence emerged as significant challenges. Many studies reported challenges in provisions for routine services and increased anxiety, fear, and stress among women. The findings highlighted that pandemic have a significant impact on women's health. Women must have equal rights and opportunities without discrimination, which requires urgent action to enhance women's rights and to achieve SDGs. Women engagement/involvement in pandemic-related services needs to be explored, which will aid in developing strategies to alleviate vulnerabilities.